Raster electron microscopy in the analysis of plant raw materials of virgin grapes (Parthenocissus quinquefolia (L.) Planch.) - F. D. Evsikov; A. A. Gudkova; A. I. Slivkin (Разработка и регистрация лекарственных средств, 2024)
Introduction. Virgin grape (maiden grape, Virginia grape, virgin grape, Parthenocissus quinquefolia (L.) Planch.) is currently used primarily for decorative purposes, but is also beginning to attract scientists from different countries as a promising source of important compounds such as anthocyanins, flavonoids, organic acids, macro- and microelements. To introduce a plant into medical practice, one of the first steps is the need to develop regulatory documentation that allows for quality assessment and standardization of plant materials, and the first stage of this process is the assessment of the characteristics of the authenticity of the object.Aim. Establish the morphological characteristics of the leaf and petiole of the virgin grape (Parthenocissus quinquefolia (L.) Planch.).Materials and methods. The object of the study was developed leaves of the virgin grape, harvested in the Voronezh region in the summer of 2022 and dried in the shade. To carry out the experiment, a JSM-6510LV electron microscope was used; the analysis was carried out after sputtering a thin film of gold onto the sample.Results and discussion. For the first time, the main structural features of various morphological features of the leaf blade of the virgin grape were identified, differences in the morphological picture of the upper and lower sides of the leaf were established, and structural features of the surface of the petiole were identified. Using micro-X-ray analysis, it was revealed that calcium and potassium are present in large quantities in the leaves and petiole of virgin grapes. The least amount of the studied elements in the study object contains magnesium. It has been shown that the leaves contain a small amount of chlorine, and the cellular contents of the petiole include a small amount of sodium.Conclusion. For the first time, a study of the morphology of the surface of the leaf blade and petiole of the virgin grape was carried out using scanning electron microscopy. The main diagnostic features of plant raw materials have been identified and visualized. Micro-X-ray structural analysis made it possible to establish the composition of the elements of the leaf blade and petiole of virgin grapes and revealed the ability to concentrate calcium, potassium, and phosphorus.